2021
DOI: 10.1177/00224669211018861
|View full text |Cite
|
Sign up to set email alerts
|

Resettlement Education Case Managers’ Roles Supporting Refugee Families With Children With Disabilities

Abstract: Refugees have been resettling in the United States for decades, but there has been little attention in the special education literature to this population. The existing literature notes numerous systemic barriers refugee families and professionals encounter but has not investigated the roles of professionals in refugee resettlement agencies in supporting families who have children with disabilities. In this study, we used semi-structured interviews to explore resettlement education case managers’ (ECMs) roles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…The literature also highlighted parental/familial support. Adams and Santos (2021) and Beatson (2013) found there was a need for parents to actively monitor their child’s education and progress, as well as health issues. As well, a clear need to empower families to advocate for themselves was evident in the literature, and it was found that often parent advocacy was the way that children were given the professional support and programming they needed (Adams and Santos, 2021; Beatson, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The literature also highlighted parental/familial support. Adams and Santos (2021) and Beatson (2013) found there was a need for parents to actively monitor their child’s education and progress, as well as health issues. As well, a clear need to empower families to advocate for themselves was evident in the literature, and it was found that often parent advocacy was the way that children were given the professional support and programming they needed (Adams and Santos, 2021; Beatson, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Adams and Santos (2021) and Beatson (2013) found there was a need for parents to actively monitor their child’s education and progress, as well as health issues. As well, a clear need to empower families to advocate for themselves was evident in the literature, and it was found that often parent advocacy was the way that children were given the professional support and programming they needed (Adams and Santos, 2021; Beatson, 2013). This theme is found throughout the literature and Cummings and Hardin (2017) highlighted that while many parents actively participated in their child’s life at home, they often participated passively at school/medical settings, often expressing that they believed the professionals to be experts.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations